How Far Can BIM Reduce Information Asymmetry in the Australian Construction Context?. Issue 3 (June 2015) - Forsythe, Perry; Sankaran, Shankar; Biesenthal, Christopher
Building Information Modeling (BIM) systems are increasingly used in construction projects. Theoretically, these systems provide greater transparency and access to construction project information and, in doing so, should reduce the information asymmetry that commonly arises in construction contracting relationships. This typically occurs when suppliers of products and services opportunistically take advantage of the client due to the imbalance in information. The article therefore explores whether or not the high level of information content offered by BIM and the potential for sharing that information among contracting parties means that the information asymmetry can be alleviated using BIM. In order to investigate this, evidence was collected through three purposively sampled case studies of large principal organizations undertaking projects in Australia—each representing a different type of customer in the supply chain on construction projects. Our findings suggest a gap between the theoretical potential and practical application of BIM to reduce information asymmetry. The study found that, although BIM has the capability to reduce information asymmetry, it has not reached a mature enough stage in the Australian construction industry to clearly confirm that it actually reduces the problem. There is even a degree of evidence that, under certain circumstances, a reverse asymmetry may exist in which a client has the technical knowledge to more successfully analyze the BIM model (relative to the organizations they contract with) and then use the resulting information to their own opportunistic advantage.